Relationship between perfectionism and depression among ASASIpintar students - Faieza Samat,; Nurul Izzati Mohd Zaidi,; Tengku Elmi Azlina Tengku Muda, (Pusat Pengurusan & Pembangunan Mahasiswa, Universiti Kebangsaan Malaysia, 2019)
For pre-university students, good academic results are vital in the pursuit of tertiary education. Often, the process of attaining academic excellence has made high-expectancy students aim for better results compared to their peers. As not all high-expectancy students manage to get their expectations, the failure may lead them to depression. This study investigated the intensity of perfectionism and the level of depression among a group of pre-university students and the relationship between the two variables. A total of 180 ASASIpintar students of session 2017/2018 at GENIUS@Pintar National Gifted Centre, Universiti Kebangsaan Malaysia had participated in this study. The findings demonstrated that the intensity of perfectionism and level of depression in ASASIpintar students was moderate. Both variables were strongly positive correlated while the perfectionism dimension that was found to play the most significant role in causing depression was socially prescribed perfectionism. Other than that, ASASIpintar students had high level of self-oriented perfectionism. In conclusion, ASASIpintar students had moderate level of depression and it was strongly related to the tendency of the students to believe that others expected perfection from them. Hence, ASASIpintar students should practice perfectionism coping strategies to avoid depression.